欧债危机对中国经济的影响——基于欧债危机演进测度的研究 =The Influence of European Debt Crisis on China’s Economy——Based on the Method of European Debt Crisis Description /张梦露; 吴凤. - 张, 梦露.
The European sovereign debt crisis transmitted to China through trade channels,financial channels and noncontact way.Refer to Lumsdaine and Prasad’s method,we build an unilateral quantity index which can describe the debt crisis.Subsequently,using VAR model studies the European debt crisis brought what kind of impact to Chinese economy.Our empirical research is based on monthly data between January 2010 and September 2014.As shown in the empirical results,debt crisis has a negative effect on Chinese macro economy.Due to the decline in external demand brought by the Europe debt crisis,China’s export industry was affected at first time.Because of the effect to the European debt crisis on China’s economy,the RMB real effective exchange rate rise.Besides,the influence of the crisis to Chinese financial industry was not significant.Finally,policy suggestions such as adjustment of economic structures,promoting the internationalization of the RMB,accelerating diversification of foreign exchange reserves,strengthening the ability of financial industry to prevent the global risk are put forward.